Intraoperative confocal laser endomicroscopy for brain tumors - potential and challenges from a neuropathological perspective - Maragkou, Theoni; Quint, Karl; Pollo, Bianca; Hewer, Ekkehard (Free Neuropathology, 2022)
Confocal laser endomicroscopy (CLE) represents a new non-invasive in vivo imaging technique that holds considerable promise in neurosurgery and neuropathology. CLE is based on the principle of optical sectioning which uses pinholes placed in the light path to selectively image photons of a specific focal plane by filtering out photons above and below the focal plane. Potential indications of CLE in neurosurgery and neuropathology include intraoperative tumor diagnosis and staging as well as assessment of tumor resection margins notably in the case of diffusely infiltrating gliomas. CLE-based tumor analysis in near-real time may also have a significant impact on future tumor resection strategies. We here discuss the technical features of CLE, its potential for wide-field imaging, its role in comparison to established histological techniques for intraoperative tumor assessment and its position in digital pathology and telepathology. Based on our group’s experience with a commercially available confocal laser endomicroscope (ZEISS CONVIVO), we critically address the current state of intraoperative CLE in brain tumor surgery, the applicability of classical histological criteria and the strategies required to further improve the diagnostic accuracy of CLE. We finally discuss how a widespread use of CLE in neurosurgery may modify the role of neuropathologists in intraoperative consultation, generating both new opportunities and new challenges.